Mode I and Mode II interfacial fracture energy of SiC/BN/SiC CMCs. (15th August 2021) - Gavalda-Diaz, Oriol; Manno, Riccardo; Melro, Antonio; Allegri, Giuliano; Hallett, Stephen R.; Vandeperre, Luc; Saiz, Eduardo; Giuliani, Finn
Abstract: Quantifying the mixed mode fracture toughness of interfaces in ceramic matrix composites (CMCs) is crucial for understanding their failure. In this work we use in situ micromechanical testing in the scanning electron microscope to achieve stable interfacial crack propagation in Mode I (Double Cantilever Beam) and Mode II (Push out) and measure the corresponding fracture resistances. We use this approach to measure the interfacial fracture resistance in SiC/BN/SiC CMCs and compare it to the fracture energy of the fibres. During in-situ testing, fracture paths can be observed while data is acquired simultaneously. We clearly observe debonding at the BN-fibre interface (i.e. inside adhesive debonding). The critical energy release rate of the BN-fibre interface for Mode I and II (GI c ≈ 2.1 ± 1.0 J/m 2 and GII c ≈ 1.2 ± 0.5 J/m 2 ) are equivalent and is lower than that measured for the fibre using microscopic DCB tests (GI c ≈ 6.0 ± 2.0 J/m 2 ). These results explain the generalized fibre debonding and pull out observed in the fracture of these CMCs. By enabling direct observation of crack paths and quantifying the corresponding fracture energies, we highlight possible routes for the optimisation and modelling of the new generation of CMC interphases. Graphical abstract: Image, graphical abstract